Strategi Guru Mengenalkan Buku Untuk Pengembangan Literasi Anak Di Tk Hardika Jaya - Trina Des; Dian Kresnawati (Universitas Pendidikan Ganesha, 2023)
Abstract The literacy level in Indonesia is relative low. However, different conditions show that parents want their children to be able to read and write before entering primary education. This is challenge for teachers at the early childhood education level to choose appropriate learning strategies to build a culture of literacy in Hardika Jaya Kindergarten. This research is descriptive research with a qualitative approach. The subjects of this study were five teachers at Hardika Jaya Kindergarten. This study use the documentation method with research instrumens in the form of questionnaires and observations sheets. The research data were analyzed using a qualitative descriptive method, which include data collection, data reduction, data presentation, and data verification. Then triangulation of data, researchers, and theory was carried out. The results showed that teachers used direct strategies to introduce books to children through observing books, reading, telling stories, playing role, asking questions, and motivating children. The facilities and infrastructure provided by the school are good enough to support children’s literacy activities. Keyword: strategist; literacy; book; early childhood education.